DC offset estimation‐based fault detection in transmission line during power swing using ensemble of decision tree. Issue 2 (1st March 2019) - Shukla, Sunil K.; Koley, Ebha; Ghosh, Subhojit
Abstract : The nuisance tripping of distance relay during power swing has been identified as one of the major causes for power system blackouts. Avoiding the risk of maloperation of distance relay and hence improving resilience during power swing, demands the development of a scheme capable of generating blocking signal during power swing and detecting a fault occurring with power swing from the measurement of current signal. In this regard, a protection scheme based on the hybrid framework of an ensemble of the tree, least square, and Adaline algorithm to perform the task of fault detection/classification, zone identification, location estimation, and power swing detection is proposed. The proposed scheme is based on the online estimation of DC offset information along with the fundamental component of the current signal. The performance of the proposed scheme has been analysed for diverse power swing and fault scenarios for two‐machine system and Western System Coordinating Council 9‐bus system. The simulation results reflect the effectiveness of the developed scheme in terms of sensitivity and reliability. Furthermore, to authenticate the effectiveness of the proposed scheme for practical scenarios, implementation, and validation of the proposed scheme has been carried out in a real‐time environment using the OPAL‐RT digital simulator.